Spirit possession: multidisciplinary approaches to a worldwide phenomenon - Pócs, Éva; Zempléni, Andras (Central European University Press, 2022)
"Possession, a seemingly irrational phenomenon, has posed challenges to generations of scholars rooted in Western notions of body-soul dualism, self and personhood, and a whole set of presuppositions inherited from Christian models of possession that was "good" or "bad." The authors of the essays in this book present a new and more promising approach. They conceive spirit possession as a form of communication, of expressivity, of culturally defined behavior that should be understood in the context of local, vernacular theories and empiric reflections. With the aim of reformulating the comparative anthropology of spirit possession, the editors have opened corridors between previously separate areas of research. Together, anthropologists and historians working on several historical periods and in different European, African, South American, and Asian cultural areas attempt to redefine the very concept of possession, freeing it from the Western notion of the self and more clearly delineating it from related matters such as witchcraft, devotion, or mysticism. The book also provides an overview of new research directions, including novel methods of participant observation and approaches to spirit possession as indigenous historiography"--